Cable-Driven Parallel Robots Proceedings of the 7th International Conference on Cable-Driven Parallel Robots - Lau, Darwin; Pott, Andreas; Bruckmann, Tobias (Mechanisms and Machine Science, 2025)
XII, 412 p. 204 illus., 179 illus. in color.